KEINFORMATIFAN LABA DI PASAR OBLIGASI DAN SAHAM: UJI LIQUIDATION OPTION HYPOTHESIS - CANDRA SARI, RATNA; ZUHROHTUN, ZUHROHTUN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 1 (2008))
Previous empirical research on informativeness of earnings has focused on stockholders, and has not examined earnings informativeness for stockholders and bondholders. Stockholders are residual claimants and bondholders are fixed claimants, the informativeness of earnings should differ for these two types of investors. When firm is financially strong, earnings changes should be of limited relevance to bondholders, but should be relevance to bondholders. In contrast, as the likelihood of financial distress increase, stockholder’s limited liability allows them to abandon the firm to bondholder and earnings change should be increasingly important to bondholders and less important to shareholders because earnings provide information on firm value. This suggest that the effect of earnings to stock return should decrease as the firm’s financial strength declines, while the effect of earnings to bond return should increase. In contrast, when firm’s financial condition is strong, the effect of earnings to stock return is higher than the effect of earnings to bond return. We refer to this as the liquidation option hypothesis. The objective of this study is to examine liquidation option hypothesis. We use bond rating as financial condition’s measurement. Consistent with our hypotheses, we find that the effect of unexpected earnings to stock return is significant when firm is financially strong but the effect of unexpected earnings to bond return is not significant. When financial distress increase, the effect of unexpected earnings to stock return is not significant but the effect of unexpected earnings to bond return is significant
Keywords: earnings, liquidation option hypothesis, bond returns, stock returns, informativeness of earnings